Fibrinogen activates focal adhesion kinase (FAK) promoting colorectal adenocarcinoma growth. (19th July 2021) - Sharma, Bal Krishan; Mureb, Duaa; Murab, Sumit; Rosenfeldt, Leah; Francisco, Brenton; Cantrell, Rachel; Karns, Rebekah; Romick‐Rosendale, Lindsey; Watanabe‐Chailland, Miki; Mast, Jacob; Flick, Matthew J.; Whitlock, Patrick W.; et al.
Abstract: Background: We previously showed that fibrinogen is a major determinant of the growth of a murine model of colorectal cancer (CRC). Objective: Our aim was to define the mechanisms coupling fibrin(ogen) to CRC growth. Results: CRC tumors transplanted into the dorsal subcutis of Fib − mice were less proliferative and demonstrated increased senescence relative to those grown in Fib + mice. RNA‐seq analyses of Fib + and Fib − tumors revealed 213 differentially regulated genes. One gene highly upregulated in tumors from Fib − mice was stratifin, encoding 14‐3‐3σ, a master regulator of proliferation/senescence. In a separate cohort, we observed significantly increased protein levels of 14‐3‐3σ and its upstream and downstream targets (i.e., p53 and p21) in tumors from Fib − mice. In vitro analyses demonstrated increased tumor cell proliferation in a fibrin printed three‐dimensional environment compared with controls, suggesting that fibrin(ogen) in the tumor microenvironment promotes tumor growth in this context via a tumor cell intrinsic mechanism. In vivo analyses showed diminished activation of focal adhesion kinase (FAK), a key negative regulator of p53, in Fib − tumors. Furthermore, nuclear magnetic resonance–based metabolomics demonstrated significantly reduced metabolic activity in tumors from Fib − relative to Fib + mice. Together, these findings suggest that fibrin(ogen)‐mediated engagement of colon cancer cells activates FAK, which inhibits p53 and its downstream targets including 14‐3‐3σ and p21, thereby promoting cellular proliferation and preventing senescence. Conclusions: These studies suggest that fibrin(ogen) is an important component of the colon cancer microenvironment and may be exploited as a potential therapeutic target.